Time-to-recovery from severe pneumonia and its predictors among children 2–59 months of age admitted to the pediatric ward of Jimma University Medical Center, Southwest Ethiopia, 2023: A retrospective cohort study - Getu Girma Bekele; Tola Getachew Bekele; Masrie Getnet; Dawit Regassa (PLoS ONE, 2025)
Background Pneumonia is an inflammation of lung parenchyma. The World Health Organization estimated 156 million cases of pneumonia occur annually. Out of them, 20 million cases severe enough to require hospitalization, and each year 1.2 million deaths occur among under-five children. Despite studies and initiatives aimed at reducing pneumonia related deaths in children, Ethiopia is ranked sixth among top fifteen countries in terms of pneumonia related morbidity and mortality. Objectives This study aimed to assess the time to recovery from severe pneumonia and its predictors among children aged 2–59 months admitted to the pediatric ward of Jimma University Medical Center; Southwest, Ethiopia, 2023. Methods A facility-based retrospective cohort study was carried out among 426 children aged between 2 and 59 months. Five years of medical records, from 2018–2022, were reviewed. A simple random sampling technique was used. Data entry was done in Epidata version 4.6 and exported to and analyzed by STATA version 15. Variables with p-value <  0.25 at Bivariable Cox regression analysis were selected for the multivariable Cox proportional model. A multivariable Cox regression model with 95% confidence interval and Adjusted Hazard Ratio was used to identify a significant predictor of time to recovery at a p-value <  0.05. Result The median recovery time was 4 days (IQR: 3, 7). Incidence rate of recovery was 15.78 per 100-person day (95% CI 14.2–17.5). The presence of co-morbidity (AHR; 0.7, 95% CI (0.54–0.91)), being treated with Ceftazidime and Vancomycin (AHR; 0.29, 95% CI (0.14–0.60)), antibiotic change (AHR; 0.74, 95% CI (0.58–0.95)) and late presentation to the Hospital (AHR; 0.58, 95% CI (0.43–0.78)) were statistically significant predictors that prolong recovery time. Conclusion The median recovery time was longer than other similar studies. Therefore, due attention should be given to the identified predictors of the recovery time.